2021
DOI: 10.1128/jvi.01257-21
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Transcriptional Footprint Is Essential for SARS-CoV-2 Replication

Abstract: SARS-CoV-2, the etiological agent of COVID-19, is characterized by a delay in Type I interferon (IFN-I)-mediated antiviral defenses alongside robust cytokine production. Here we investigate the underlying molecular basis for this imbalance and implicate virus-mediated activation of NF-κB in the absence of other canonical IFN-I-related transcription factors. Epigenetic and single cell transcriptomic analyses show a selective NF-κB signature that was most prominent in infected cells. Disruption of NF-κB signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 72 publications
31
91
0
Order By: Relevance
“…One consequence of this drastic shutoff is the suppression of expression of innate immune genes, such as IFN type I and type III. In agreement with previous RNA-seq studies performed in bulk population of infected A549-ACE2 cells [19,38] and kidney HEK293T-ACE2 cells [59], our transcriptomic profiling combined with analysis of mRNA levels and IFN secretion showed that infected cells failed to mount an antiviral response. Besides global gene expression reduction in host cells, SARS-CoV-2 has evolved numerous mechanisms to specifically counteract the IFN induction and signaling pathways [14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One consequence of this drastic shutoff is the suppression of expression of innate immune genes, such as IFN type I and type III. In agreement with previous RNA-seq studies performed in bulk population of infected A549-ACE2 cells [19,38] and kidney HEK293T-ACE2 cells [59], our transcriptomic profiling combined with analysis of mRNA levels and IFN secretion showed that infected cells failed to mount an antiviral response. Besides global gene expression reduction in host cells, SARS-CoV-2 has evolved numerous mechanisms to specifically counteract the IFN induction and signaling pathways [14].…”
Section: Discussionsupporting
confidence: 90%
“…2C). This difference explains why IL32 was not identified as an up-regulated gene in previous RNA-seq analysis performed in mixed population of infected A549-ACE2 cells [19,38]. Similarly, the expression of ITGAM, TRAF1, WAKMAR2, AL132990.1 and XLOC_007519 showed a modest increase of mRNA abundances in the bulk population and a significant increase in S + cells, as compared to mock-infected cells (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…To corroborate the clinical validity of the SARS-CoV-2 acute hamster data, we compared our RNA-seq analyses to published results from lungs of COVID-19 deceased individuals that still had high viral loads at the time of death (Figure 2A-C) (Butler et al, 2021). In agreement with the published data, we find transcriptional signatures from both groups were dominated by a marked upregulation of the IFN-I response as well as TNFα signaling via NFκB (Blanco-Melo et al ., 2020; Hoagland et al ., 2021; Nilsson-Payant et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These differences likely reflect the unique biologies of the viruses. SARS-CoV-2 generates significantly more double stranded RNA (dsRNA) during its life cycle as a result of sgRNA production (Nilsson-Payant et al ., 2021; Perlman et al, 1986). Given the immunogenicity and stability of dsRNA, it seems reasonable to postulate that comparable levels of replication would result in a more robust immune response to SARS-CoV-2 as compared to IAV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation